2014
DOI: 10.1016/j.agrformet.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven diagnostics of terrestrial carbon dynamics over North America

Abstract: a b s t r a c tThe exchange of carbon dioxide is a key measure of ecosystem metabolism and a critical intersection between the terrestrial biosphere and the Earth's climate. Despite the general agreement that the terrestrial ecosystems in North America provide a sizeable carbon sink, the size and distribution of the sink remain uncertain. We use a data-driven approach to upscale eddy covariance flux observations from towers to the continental scale by integrating flux observations, meteorology, stand age, abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 85 publications
8
88
3
1
Order By: Relevance
“…1), a global network that measures the exchanges of carbon dioxide, water vapor, and energy between the biosphere and atmosphere (Baldocchi et al, 2001). The FLUXNET data (Baldocchi et al, 2001;Baldocchi and Ryu, 2011) have been widely used to understand the evapotranspiration processes and trend (Jung et al, 2010;Fang et al, 2015), develop AET and ecosystem models (Sun et al, 2011b; et al, 2016), and map continental-scale ecosystem productivity (Xiao et al, 2014;Zhang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…1), a global network that measures the exchanges of carbon dioxide, water vapor, and energy between the biosphere and atmosphere (Baldocchi et al, 2001). The FLUXNET data (Baldocchi et al, 2001;Baldocchi and Ryu, 2011) have been widely used to understand the evapotranspiration processes and trend (Jung et al, 2010;Fang et al, 2015), develop AET and ecosystem models (Sun et al, 2011b; et al, 2016), and map continental-scale ecosystem productivity (Xiao et al, 2014;Zhang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Cubist was used because of its use of generalized rules and widespread successful applications in the remote sensing field [5,10,11,14,18,[42][43][44][45][46][47][48][49][50][51]. Each regression tree model consisted of the dependent variable to be estimated and the set of independent variables.…”
Section: Regression Tree Model Developmentmentioning
confidence: 99%
“…Although a flux tower measures only its surrounding vicinity, numerous studies have shown that these recordings can be used in regional or land cover specific synthesis [3,4] or up-scaled to much greater levels through analyses of geospatial data relationships using computer modeling [9,13,18]. Of particular interest is the use of data mining regression tree algorithms for carbon flux mapping [5,10,11,13,14,18]. An acute capability to address nonlinear relationships, deal with complex high order interactions, easily interpret results, and utilize both categorical and continuous variables, lends data mining regression tree [10], which contrasts with process-based modeling approaches that are frequently heavily driven by precipitation, a difficult variable to map accurately, particularly in rural regions where weather stations are sparse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations